Identifikasi Potensi Wisata Situs Gua Song Gilap Di Pracimantoro, Wonogiri, Jawa Tengah - Raden Al Huda Belva A.W; Wiwik Setyaningsih; Purwanto Setyo Nugroho; Ana Hardiana; Ofita Purwani (Universitas Sebelas Maret Surakarta, 2021)
Wonogiri regency has a huge potency, especially in its natural wealth. Limestone sites are very easy to find in wonogiri regency, but there are still many limestone sites that are not optimally managed so it is feared to be damaged and lost. The local government provides considerable support in developing the potency of the region in the field of tourism. Song Gilap Cave is one of the cave sites that has tourism potency in Wonogiri Regency, especially in Pracimantoro District. The purpose of this research is to map the tourism potency in Song Gilap Cave so that it can be developed optimally. The method of maping tourism potency in this research was carried out with SWOT analysis that discussed the strengths, weaknesses, opportunities, and threats at the site of Song Gilap Cave. The mapping resulted in several strategies for the development of the Song Gilap Cave site area which is expected to maximize the natural potential so that it can be a forum for the surrounding community to develop themselves in the education, conservation, economic, social, and cultural fields.